2020
DOI: 10.1038/s41598-020-77753-0
|View full text |Cite
|
Sign up to set email alerts
|

Gallium phosphide optical metasurfaces for visible light applications

Abstract: There are few materials that are broadly used for fabricating optical metasurfaces for visible light applications. Gallium phosphide (GaP) is a material that, due to its optical properties, has the potential to become a primary choice but due to the difficulties in fabrication, GaP thin films deposited on transparent substrates have never been exploited. In this article we report the design, fabrication, and characterization of three different amorphous GaP metasurfaces obtained through sputtering. Although th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…The poor crystallinity of GaP layers grown in a single step at low T gr also results in a lower value of the optical density for wavelengths shorter than 450 nm and below band gap optical losses. We attribute the observed red shift of the optical absorption coefficient (Figure c) to 1.94 eV to the effect of crystal structure defects, as were reported earlier. ,, Meanwhile, the refractive index value and dispersion behavior in the below band gap region (500–1700 nm) of the obtained GaP layer correspond to bulk material properties.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The poor crystallinity of GaP layers grown in a single step at low T gr also results in a lower value of the optical density for wavelengths shorter than 450 nm and below band gap optical losses. We attribute the observed red shift of the optical absorption coefficient (Figure c) to 1.94 eV to the effect of crystal structure defects, as were reported earlier. ,, Meanwhile, the refractive index value and dispersion behavior in the below band gap region (500–1700 nm) of the obtained GaP layer correspond to bulk material properties.…”
Section: Resultssupporting
confidence: 82%
“…Other reported approaches for GaP growth on silica, glass, or sapphire substrates by RF sputtering at elevated substrate temperatures led to the formation of polycrystalline or nanoparticulate films with a rough surface morphology. Since the increased roughness complicates the lithography and etching processes and leads to scattering losses, the above-mentioned approaches are not really compatible with photonic applications. However, the optical properties of a-GaP layers can be improved by postdeposition annealing. , The main disadvantage of RF sputtering compared to the epitaxial growth approach is the random orientation of GaP layer crystallites in the film plane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gallium phosphide (GaP) is another material that has recently gained substantial attention in metasurface-based nanophotonic applications. , GaP shows negligible linear absorption over the visible range, and GaP nanoantennas and metasurfaces have been used for visible-light applications as well as for enhancement of nonlinear second-harmonic generation (SHG). , Moretti et al recently reported GaP metasurfaces for efficient photonic and spectroscopic applications . Although GaP metasurface modifications for sensing applications are not frequently found or implemented in the literature, here we report a few functionalization routes successfully used on GaP surfaces that could be applicable to GaP metasurface sensors.…”
Section: Surface Functionalizationmentioning
confidence: 92%
“…Gallium phosphide (GaP) is another material that has recently gained substantial attention in metasurface-based nanophotonic applications. 150,151 GaP shows negligible linear absorption over the visible range, and GaP nanoantennas and metasurfaces have been used for visible-light applications 151 as well as for enhancement of nonlinear second-harmonic generation (SHG). 150,152 Moretti et al recently reported GaP metasurfaces for efficient photonic and spectroscopic applications.…”
Section: Chemicalmentioning
confidence: 99%